2023
DOI: 10.4103/1673-5374.363185
|View full text |Cite
|
Sign up to set email alerts
|

Investigational treatments for neurodegenerative diseases caused by inheritance of gene mutations: lessons from recent clinical trials

Abstract: We reviewed recent major clinical trials with investigational drugs for the treatment of subjects with neurodegenerative diseases caused by inheritance of gene mutations or associated with genetic risk factors. Specifically, we discussed randomized clinical trials in subjects with Alzheimer’s disease, Huntington’s disease and amyotrophic lateral sclerosis bearing pathogenic gene mutations, and glucocerebrosidase-associated Parkinson’s disease. Learning potential lessons to improve future therapeutic approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Solanezumab, which only binds soluble monomers, recognizes residues 13 to 24 of Aβ42 [26]. Crenezumab recognizes residues 13 to 24 of Aβ42 and has a high affinity for the oligomeric form [26][27][28]. Because of the distinct abilities of these mAbs, corresponding scFvs, scFv-C, scFv-S, and scFv-12B4 were designed and constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Solanezumab, which only binds soluble monomers, recognizes residues 13 to 24 of Aβ42 [26]. Crenezumab recognizes residues 13 to 24 of Aβ42 and has a high affinity for the oligomeric form [26][27][28]. Because of the distinct abilities of these mAbs, corresponding scFvs, scFv-C, scFv-S, and scFv-12B4 were designed and constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Gene editing technologies have been explored to correct certain presenilin mutations [115]. Recent studies have shown that CRISPR-Cas9 gene editing technology is able to selectively disrupt PSEN1 mutations leading to an autosomal dominant form of early-onset AD and counteract the AD-associated phenotype [116,117]. Despite challenges, targeting the γ-secretase complex, especially presenilin, remains a therapeutic focus in AD research.…”
Section: Treatment and Research Progressmentioning
confidence: 99%
“…Lack of efficacy is one of the main reasons NATs fail in clinical trials [ 21 ]. Two recent examples of failed NATs include drisapersen (an exon skipping ASO developed for Duchenne muscular dystrophy) [ 23 ] and tominersen (an ASO targeting the mutated transcript in Huntington’s Disease) [ 24 ]. Despite demonstrating promising efficacy in two independent phase II trials, drisapersen development was terminated following its phase III trial as the treatment failed to significantly slow disease progression.…”
Section: Challenges With Developing Nucleic Acid Therapeutics For Mye...mentioning
confidence: 99%